High step‐up DC–DC converter using one switch and lower losses for photovoltaic applications. Issue 13 (3rd September 2018) - Maalandish, Mohammad; Hosseini, Seyed Hossein; Jalilzadeh, Tohid; Vosoughi, Naser
Abstract : In this study, a new non‐isolated high step‐up dc–dc converter using one switch and low‐voltage stress on semiconductors is presented for photovoltaic applications. The proposed converter consists of one switch in the input side ( S ), voltage multiplier units (D–C–L), one diode in the output side ( D o ) and one capacitor ( C o ). To achieve high‐voltage gain and power level, the proposed converter can be extended to n stages of voltage multiplier units. Hence, the output voltage level will be reasonably increased and the nominal value of power devices will be decreased. Therefore, the voltage stress across the power switch is decreasing for different duty cycles at high power levels. As a result, the efficiency of the proposed converter can be increased by using one switch with lower resistance r DS(on) . To verify the carried mathematical analysis of the proposed converter and circuit implementation are validated through both the simulation and experimental results that accordance each other well. The experimental results of two prototypes (with n  = 2, 3) in about 290 W operating at 33 kHz are provided.